Efektivitas Pengajaran Mikro Di Stain Samarinda - Etty Nurbayani (LP2M UIN Sultan Aji Muhammad Idris Samarinda, 2012)
The objective of this research is to know the effectiveness of micro-teaching in STAIN Samarinda and to know the implementation of micro-teaching in STAIN Samarinda. The population of the study is the seventh semester students of PAI program study and the fifth semester students of English program. The data collection technique is questionnaires, documentation, observation, and interview. The questionnaires concists of some questions to the students are to find out 3 indicators; effective, less effective, and not effective. Documentation was used to find out the students’ achievement who took micro-teaching. Observation was used to observe the implementation of micro-teaching. Interview was used to find out the process of micro-teaching and the students’ respond in the class of micro-teaching. Data were tabulated, scored, and counted to get the procentage, then analyzed to draw conclusion. Data analyzed based on the result of tabulation. The findings show that micro-teaching of Tarbiyah of STAIN Samarinda is effective and could show the students’ ability in teaching.